Islamic Perspective on Creative Marine Ecotourism Development Policy in Kalanganyar Village Sedati Sidoarjo - M. Husni Tamrin (Universitas Muhammadiyah Malang, 2020)
This study aims to describe a development policy and supporting factors, and also inhibitors of marine ecotourism in Kalanganyar Village, Kalanganyar Village in Sidoarjo Regency in an Islamic perspective. This study used qualitative method with an interaction model consisting of 3 (three) activities: data reduction, data presentation, and drawing a conclusion. Data collection were obtained from direct observations at the research location and also interviews with the Sidoarjo tourism office and visitors to the marine tourism of Kalanganyar Village. The results of this study indicate that Kalanganyar Village has a variety of tourism potential, although there is still a lack of support from related agencies, such as the existence of infrastructure and service as a tourist destination. However, in broad outline the potential of the Kalanganyar village is superior in Sidoarjo Regency.